2016
DOI: 10.1080/03009742.2016.1181203
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in knee pain, knee osteoarthritis, and health-related quality of life: a population-based cohort study in southern Sweden

Abstract: In Sweden there are socioeconomic gradients related to both FKP and knee OA as well as HRQoL in favour of people with better SES. SES should be taken into account in health resource allocation pertaining to knee-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 52 publications
3
31
1
Order By: Relevance
“…Our findings that participants with lower educational attainment reported more pain and lower HRQoL at baseline and maintained a higher willingness to undergo joint surgery despite participation in the BOA self-management program is in line with earlier research [11,14,24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings that participants with lower educational attainment reported more pain and lower HRQoL at baseline and maintained a higher willingness to undergo joint surgery despite participation in the BOA self-management program is in line with earlier research [11,14,24].…”
Section: Discussionsupporting
confidence: 92%
“…Disparities in the patient reported frequency of OA-related symptoms and self-efficacy to manage symptoms have previously been reported in the Swedish context based on social determinants, such as educational level and domestic/foreign birthplace [10][11][12]. A recently published study by Kiadaliri and colleagues [11] found that Swedish residents diagnosed with knee OA who had lower educational levels had more frequent pain and worse health-related quality of life (HRQoL) than those with a higher educational level. Higher odds of symptomatic or radiologically confirmed OA as well as willingness to undergo TJR have been confirmed internationally in those with lower education [13,14].…”
Section: Introductionmentioning
confidence: 97%
“…Subjects with pain in one or both knees in the past 12 months and duration of minimum 1 month were classified as having knee pain. In the second stage of the MOA, a random sample of 1 300 subjects with knee pain and 650 subjects without knee pain were invited to a clinical visit and radiographic examination [ 13 ]. A total of 1 527 subjects participated in the second stage and responded to the EuroQol-5D-3L (EQ-5D-3L) and the Knee injury and Osteoarthritis Outcome Score (KOOS) questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Many elderly OA patients visit pain clinics or hospitals, and knee and hip OA were reportedly the third most prevalent musculoskeletal disorder . OA causes pain and is associated with physical disability . Both pain and physical disability cause a decline in the quality of life and also affect psychological health.…”
Section: Introductionmentioning
confidence: 99%